Implementasi Personal Information Management (PIM) Mahasiswa Tingkat Akhir Pada Program Studi Ilmu Perpustakaan - Yani, Eka Andria; Syam, Abdi Mubarak (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to explore the application of Personal Information Management (PIM) in final year students at the Library Science Study Program, North Sumatra State Islamic University (UINSU). By using a qualitative approach and phenomenological methods, this research seeks to understand students' experiences and awareness in managing personal information. Data was collected through in-depth interviews with six students selected using purposive sampling. The research results revealed that students face challenges in dealing with an abundance of information, which often leads to information overload. The PIM strategy implemented includes the activities of finding, storing, organizing, maintaining and managing the flow of information. However, there are significant differences in personal information management skills among students that may be due to differences in educational background and technology experience. This research emphasizes the importance of effective PIM development strategies to help students better manage their personal information. Keywords: Personal Information Management, Personal Information Management, Students, Information Overload, Information Technology. Penelitian ini bertujuan untuk mengeksplorasi penerapan Manajemen Informasi Pribadi (Personal Information Management/PIM) pada mahasiswa tingkat akhir di Program Studi Ilmu Perpustakaan Universitas Islam Negeri Sumatera Utara (UINSU). Dengan menggunakan pendekatan kualitatif dan metode fenomenologi, penelitian ini berusaha memahami pengalaman serta kesadaran mahasiswa dalam mengelola informasi pribadi. Data dikumpulkan melalui wawancara mendalam dengan enam mahasiswa yang dipilih secara purposive sampling. Hasil penelitian mengungkapkan bahwa mahasiswa menghadapi tantangan dalam menangani informasi yang berlimpah, yang sering kali menyebabkan overload informasi. Strategi PIM yang diterapkan mencakup aktivitas menemukan, menyimpan, mengorganisasi, memelihara, dan mengelola aliran informasi. Namun, terdapat perbedaan signifikan dalam keterampilan manajemen informasi pribadi di kalangan mahasiswa yang mungkin disebabkan oleh perbedaan latar belakang pendidikan dan pengalaman teknologi. Penelitian ini menekankan pentingnya pengembangan strategi PIM yang efektif untuk membantu mahasiswa dalam mengelola informasi pribadi mereka dengan lebih baik. Kata Kunci: Manajemen Informasi Pribadi, Personal Information Management, Mahasiswa, Overload Informasi, Teknologi Informasi.